Community. Season two [videorecording (DVD)] - Harmon, Dan, 1973- (Sony Pictures Home Entertainment, 2015)
From Dan Harmon comes COMMUNITY, a smart and hilarious comedy series about a band of misfits who attend Glendale Community College. Recently disbarred lawyer Jeff Winger enrolls to get a legit degree the quickest and easiest way possible, but when he starts a fake Spanish study group solely for the purpose of hooking up with a sexy classmate, he doesn't expect to be joined by a random group of misfit fellow students. Over the course of the next 6 years, this group finds themselves involved in epic paintball battles, chicken finger conspiracies, sci-fi conventions, campus-wide pillow wars, and everything in-between. In the process, they become so much more than just a study group ... they become a family.